Effect of variant transformations in fusion zones of gas metal arc welds. (11th May 2015) - Béreš, M.; Abreu, H. F. G.; Santos, L. P. M.; Davies, C. M.; Dye, D.
Abstract : The macro- and microtextures of gas metal arc welds fabricated using both conventional ferritic and low transformation temperature (LTT) filler metals were examined. Both welds were largely composed of acicular ferrite. The weld textures were found to be distinct, which is observed to be due to variant selection during the austenite to ferrite transformation. In situ electron backscatter diffraction performed during thermal cycling of the LTT fusion zone into the austenite phase field confirmed that these transformations satisfy the expected crystallographic relationships. Implications for welding consumable design and finite element process modelling are drawn.